Helicobacter pylori [electronic resource] - Fleming, Shawna L.; Alcamo, I. Edward; Heymann, David L. (Deadly diseases and epidemics, 2007)
Describes the symptoms and effects of helicobacter pylori infections--the leading cause of stomach ulcers--the role of the bacteria in harboring other diseases, how they affect digestion, and treatment options.